Determinants of Labor Migration to International Labor Markets: A Study of Sumatra Island - Atiyatna, Dirta Pratama; Hamira; Yunisvita (Faculty of Economics, Universitas Sriwijaya, 2024)
This study investigates the determinants of labor migration from Sumatra Island, focusing on key factors such as per capita income, provincial minimum wage, unemployment rates, and education levels. Using panel data from 2017 to 2021 across ten provinces, the analysis employs a random effects model to assess these variables' impact on migration patterns. The results reveal that the provincial minimum wage significantly influences labor migration, while per capita income, unemployment rates, and education levels do not show a substantial effect. Despite relatively higher wages in provinces such as Riau and West Sumatra, economic instability persists, prompting workers to seek better opportunities abroad. These findings emphasize the pivotal role of wage disparities in driving labor migration from Sumatra, particularly toward international labor markets, underscoring the need for more equitable economic policies to mitigate the pressures of outbound migration.